Underestimated reason of hyperkalemia in diabetic patients: type IV renal tubular acidosis- mini review - Sibel Ertek; Kayser Caglar (Frontiers in Clinical Diabetes and Healthcare)
Diabetes mellitus is chronic disease with increasing prevalence, and may cause many organ complications, including kidneys. Reduced creatinine clearance and kidney failure are important, but hyperkalemia may be present in diabetic patients even before these problems. There may be many reasons of hyperkalemia in this group of patients. Type IV renal tubular acidosis is important cause of generally mild hyperkalemia, and it is a treatable condition. ‘‘Polypharmacy’’ –which is very common in diabetic patients due to accompanying other diseases- may trigger electrolyte imbalance. Underlying causes should be investigated and treatment should be done before it worsens.